Cone Reconstruction in Children with Ebstein Anomaly: The Mayo Clinic Experience. (23rd December 2013) - Anderson, Heather N.; Dearani, Joseph A.; Said, Sameh M.; Norris, Mark D.; Pundi, Kavitha N.; Miller, Angela R.; Cetta, Michael L.; Eidem, Benjamin W.; O'Leary, Patrick W; Cetta, Frank
Abstract Objective Valve repair for pediatric patients with Ebstein anomaly has historically yielded varied results. The cone reconstruction (CR) first described by Da Silva has revolutionized the surgical approach to these patients. This study reports our recent experience with CR in children and young adults with Ebstein anomaly. Design Electronic medical records were reviewed for all patients < 21 years old who had surgery to repair Ebstein anomaly at Mayo Clinic Rochester between June 2007 and December 2012. Clinical data including preoperative demographics, intraoperative procedures, and postoperative outcomes were recorded. Results Eighty‐four patients initially had a cone reconstruction (54% male, mean age 10.1 ± 5.9 years). Indications for operation included cardiomegaly (42%), cyanosis (19%), and heart failure (19%). The preoperative echocardiogram demonstrated severe tricuspid regurgitation in 91% of patients. There was one early death and 3 early CR breakdowns requiring reoperation (2 re‐repair, 1 tricuspid replacement). Eighty‐two patients (98%) had successful CR at the time of hospital discharge. Patient age, gender, cardiopulmonary bypass time, and aortic cross‐clamp time were not associated with early CR failure. Use of a partial or eccentric annuloplasty ring correlated with successful initial CR (P = .01). There have been no early CR breakdowns since 2010. Follow‐up information was available for 77 patients (longest follow‐up 6.5 years; mean 0.8 ± 0.2 years). The most recent postoperative echocardiogram demonstrated mild or no tricuspid regurgitation in 83%. Tricuspid stenosis (mean gradient > 5 mm Hg) was present in 6 patients. There was one late death (motor vehicle accident) and one late re‐repair of the tricuspid valve 4 years after initial operation. Conclusions CR in children and young adults with Ebstein anomaly can be performed with low early mortality and excellent durability at short‐term follow‐up. CR represents an important surgical option for young patients. It is applicable to patients with a broad range of anatomic variability and precludes valve replacement in the vast majority. CR should be considered prior to the deleterious effects of chronic right ventricular volume overload and the development of systolic dysfunction, which hamper long‐term prognosis. Therefore, early referral for surgical evaluation is recommended.